The Role of Antibiotics in Nasal Fractures after Closed Reduction. Issue 4 (7th April 2023) - Vishwanath, Neel; Rhee, Ben; Sobti, Nikhil; Beqiri, Dardan; Xi, Kevin; Lerner, Julia; Woo, Albert S
Abstract : Background: Nasal fractures represent the most common fracture in facial trauma. The role of prophylactic antibiotics in these injuries is debated, given low infection rates and demonstrated risks of antibiotics. We studied the isolated effect of prophylactic antibiotics on infection rate in patients with nasal fracture after closed reduction. Methods: Retrospective cohort study of a prospectively maintained facial trauma database was conducted. Demographics, comorbidities, fracture classifications, and management of patients who received antibiotics at the time of closed nasal reduction were compared against those who did not receive antibiotics. Infection rates between groups were analyzed. Multivariate analysis was conducted to control for confounding variables. Qualitative analysis was performed for patients who experienced infection following nasal fracture. Results: A total of 282 patients met inclusion criteria (n = 144, antibiotic; n = 138, nonantibiotic). Six patients experienced infection. There was no difference in infection rate between antibiotic and nonantibiotic groups (2.0% versus 2.2%; P = 0.90). On multivariate regression, antibiotics did not significantly decrease odds of infection (OR 1.7 [0.17–13.6]; P = 0.64). Moreover, patients with open nasal fractures did not have significantly higher odds of infection (OR 1.9 [0.08–20.8]; P = 0.64). Similarly, increasing severity of injury based on Rohrich classification did not significantly impact odds of infection (OR 0.68 [0.23–1.9]; P = 0.46). All six infections were managed at the bedside, with zero infections following operating room management ( P = 0.32). Conclusions: Prophylactic antibiotics do not decrease infection rates following nasal fractures managed by closed reduction. Bedside management may be a risk factor for the development of infection; however, this finding requires further evaluation.